Research on Corporate Identity of Tropical Fruit Farm - Tan, Ai Chee (Universiti Malaysia Sarawak (UNIMAS), 2007)
Tropical Fruit Fann is an ideal location for cultivating many types of tropical and subtropical fruit trees. The fann does not have a strong corporate identity that will convince tourists to visit the fann, thus a new corporate identity will be created. With a strong corporate identity, "Tropical Fruit Fann" hopes to be a new attraction for locals and foreigners fruit lover.